Telestroke consultation can accurately diagnose ischemic stroke mimics. (July 2023) - Poon, Jason T; Tkach, Aleksander; Havenon, Adam H de; Hoversten, Knut; Johnson, Jaleen; Hannon, Peter M; Chung, Lee S; Majersik, Jennifer J
Introduction: Telestroke (TS) networks are standard in many areas of the US. Despite TS systems having approximately 33% mimic rates, it is unknown if TS can accurately diagnose patients with acute ischemic stroke (AIS) versus stroke mimics. Methods: We performed a retrospective review of consecutive TS consults to 27 TS sites in six states during 2018. Clinical information and diagnosis were extracted from discharge records and compared to those from the TS consult. Discharge diagnoses were verified and coded into 12 categories. Cases without a clear discharge diagnosis and intracerebral haemorrhage were excluded. We report agreement and a Cohen's kappa between TS and discharge diagnoses for the category of AIS/transient ischemic attack (TIA) versus stroke mimic. Results: We included 404 cases in the analysis (mean age 66 years; 54% women). Of these, 225 had a TS diagnosis of AIS/TIA; 102 (45%) received intravenous tissue plasminogen activator. Our study demonstrated a high diagnostic agreement for AIS/TIA (88%) with a kappa of 0.75 for stroke and mimics. Of the 179 patients diagnosed with a stroke mimic on TS, 27 (15%) were diagnosed with AIS/TA by discharge. TS mimic diagnosis had a positive predictive value (PPV) of 85% and a negative predictive value (NPV) of 90%; TS diagnosis of stroke/TIA had PPV 90%, NPV 85%. Discussion: We found excellent correlation between TS and discharge diagnoses for patients with both stroke and stroke mimics. This suggests that TS systems can accurately assess a wider variety of patients with acute neurologic syndromes other than AIS.